Hubungan Sistem Pendokumentasian Keperawatan Berbasis Elektronik dengan Kinerja Perawat di Unit Rawat Jalan Dua RSUD - Rahayu Rahayu; Maridi Marsan Dirdjo; Ulfatul Muflihah (Poltekkes Kemenkes Padang, 2024)
Documentation about of activities carried out starting from assessments, diagnoses, action plans, nursing actions and evaluations that are recorded both electronically and manually and can be accounted for. Electronic documentation greatly influences nurse performance because nurses are able to maximize the time they provide nursing care to patients. Quality electronic nursing care documentation is also influenced by the performance of nurses who are competent in providing documentation. Objective To determine the relationship between the electronic-based nursing documentation system and the performance of nurses in the outpatient unit of two hospitals. This type of research is descriptive correlation using a cross sectional approach. Sampling was done by Total Sampling method 71 respondens. Data collection techniques using electronic nursing documentation research questionnaires and nurse performance. Data analysis used bivariate analysis with the person product moment correlation coefficient test. The results that the Pearson product moment analysis obtained an r value of 0.682 which means that it has a strong relationship, indicating a positive direction and with a P-value of 0.000, it means that there is relationship between the electronic based nursing documentation system and the performance of nurses in the outpatient units of two hospitals.This research concludes that there is a relationship between an electronic-based nursing documentation system and the performance of nurses in the outpatient units of two regional hospitals. It is hoped that this research will be a reference for further researchers regarding electronic documentation systems and nurse performance.